Development of a micro-thruster system for an advanced nano-satellite - Pee, Xiu Yi. (2012)
Developing a thruster system for Velox-1 class nanosatellites allows for additional possibilities with regards to attitude determination and control and orbital manoeuvres. It expands the capabilities and robustness of the satellite system. In this project a thruster system was examined and sized for a 3-6 month station-keeping mission.